A PRELIMINARY STUDY OF THE MANGROVE FOREST ON PULAU RAMBUT, JAKARTA BAY - Kartawinata, Kuswata; Walujo, Eko B. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1977)
Pulau Rambut (Â± 56ha) is one of the islands of the Pulau Seribu group. It is a coral island covered by disturbed forest and secondary growth at the center, and mangrove forest at its periphery. A study in a 290 x 10 m transect running south to north across the mangrove forest shows a distinct zonation as follows : the Scyphiphora hydrophyllacea - Lumnitzera racemosa community on coral flat with patchy shallow soils on the interior, the Rhizophora mucronata community on relatively deep soil overlaying coral formation, and the R. mucronata - R. stylosa community on periodically submerged coral flat. Profile diagrams established along the transect show structural changes also. The R. mucronata forest is the most developed community and appears to be the most prevalent. R. stylosa forms the pioneer species on this island.